2006
DOI: 10.1038/nature05296
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Complete photo-fragmentation of the deuterium molecule

Abstract: Nature 431, 437--440 (2004) In Figs 2 and 3 of this Letter, we calculated the angle between the molecular axis and the in-plane electron as Q e,mol 5 Q mol -Q e , where Q e and Q mol are the angles of the electron and the molecular axis with respect to the polarization vector e. This distribution was then rotated by the angle of the molecular axis to picture the electron emission in the polar plots. Here a sign error occurred: instead of calculating and plotting Q mol -Q e,mol 5 Q e , we presented Q mol 1 Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…Indeed, in the independent electron model, the double ionization probability is zero, which is the consequence of both the exact orthogonality of the atomic or molecular orbitals and the one-body character of the dipole operator. For the case of H 2 , the simplest molecular target, double photoionization (DPI) is accompanied by a Coulomb explosion of the nuclei, and recent momentum imaging experiments [1][2][3][4] in which all four charged particles are measured in coincidence have shown that the correlated motion of the ejected electrons is sensitive to the kinetic energy release (KER) of the dissociating nuclei. The KER, as we verify below, is directly related to the internuclear separation of the target at the moment of photon absorption via the relation KER 1=R.…”
mentioning
confidence: 99%
“…Indeed, in the independent electron model, the double ionization probability is zero, which is the consequence of both the exact orthogonality of the atomic or molecular orbitals and the one-body character of the dipole operator. For the case of H 2 , the simplest molecular target, double photoionization (DPI) is accompanied by a Coulomb explosion of the nuclei, and recent momentum imaging experiments [1][2][3][4] in which all four charged particles are measured in coincidence have shown that the correlated motion of the ejected electrons is sensitive to the kinetic energy release (KER) of the dissociating nuclei. The KER, as we verify below, is directly related to the internuclear separation of the target at the moment of photon absorption via the relation KER 1=R.…”
mentioning
confidence: 99%
“…The effect is most apparent in the full 3D plots. As Weber et al [72] point out, in the analogous atomic case of helium the light field apparently drives electrons towards a dipole pattern keyed to the axis of polarization, whereas in the geometry of the experiment shown in Fig. 3 the molecule emits the in-plane electron strongly perpendicular to its axis.…”
Section: Double Photoionization Of Hmentioning
confidence: 97%
“…Experiments in which both electrons are ejected from an oriented hydrogen molecule by absorption of a single photon are currently available [9,[71][72][73]. Among the latter, Weber et al [9,72] have recently demonstrated that the ejection pattern of the electrons depends sensitively on the bond distance between the two nuclei as they vibrate in their ground state.…”
Section: Double Photoionization Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…This work demonstrates that attosecond coherent control methods can manipulate double ionization processes on attosecond time scales, where electron-electron interactions play an important role. Double photoionization is a fundamental mechanism where a single photon can ionize two electrons simultaneously from an atom, providing insight into electron/electron dynamical correlation processes [25][26][27][28]. Understanding and coherently controlling these correlations in simple atoms and molecules, where theoretical models are possible, will help develop the more advanced concepts necessary to control ultrafast dynamics in complex molecular systems [29] or novel, strongly-correlated materials [30].…”
mentioning
confidence: 99%